La stéréotomie en Périgord à la Renaissance : un exemple de persistances architecturales reprises par la tratadistique française du XVIe siècle - Mélanie Lebeaux (Les Cahiers de Framespa)
In 1567, Philibert de L’Orme published the first tome of L’Architecture, in which books III and IV are devoted to stereotomy, the science of carving and assembling stones. His collection of figures draws on traditional architectural forms implemented since the Romanesque era and taken over for the most part during the Renaissance. Many examples of this architectonic reality are to be found in Périgord. The transition from practice to Philibert de L’Orme’s theory is based on the analysis of three types of vault : bias arc, arc in corner and rib vault.